Pigeon Droppings as a Cryptococcus Reservoir: A Review - Esakkiammal, M; Rajakumari, D.V. Sheeba (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Cryptococcus neoformans are an encapsulated yeast and causative agent of cryptococcosis in man and animals. C. neoformans has worldwide distribution and infects immunosuppressed individuals, especially those suffering from AIDS. Cryptococcus neoformans and Cryptococcus gattii are the two species of Cryptococcus that are typically linked to human illnesses. It has been identified for its association with bird guano accumulations, particularly pigeon excrement, and has been isolated from various natural sources. The major environmental sources of Cryptococcus neoformans are soil contaminated with pigeon droppings or eucalyptus trees and decaying woods forming hollows in living trees. Pigeon droppings are a suitable environment for the growth of fungi and bacteria. Pigeon guano is a common source for infection propagules of Cryptococcus neoformans and is postulated to play a central role in transmission from the environment to humans. Pigeon dropping consists of nitrogen, phosphorus, potassium as well as other minerals. These constituents provide an excellent sanctuary that supports the growth of various microorganisms. The review emphasizes that pigeon droppings are a significant reservoir and spread site for the Cryptococcus neoformans fungus.